2021
DOI: 10.1186/s12920-021-00967-2
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive analysis of prognostic value and immune infiltration of kindlin family members in non-small cell lung cancer

Abstract: Background Kindlin Family Members have been reported to be aberrantly expressed in various human cancer types and involved in tumorigenesis, tumor progression, and chemoresistance. However, their roles in non-small cell lung cancer (NSCLC) remain poorly elucidated. Methods We analyzed the prognostic value and immune infiltration of Kindlins in NSCLC through Oncomine, GEPIA, UALCAN, CCLE, Kaplan‑Meier plotter, cBioPortal, TIMER, GeneMANIA, STRING, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 61 publications
(80 reference statements)
3
9
0
Order By: Relevance
“…So far, studies have shown that FERMT3 plays crucial roles in important physiological and pathological processes, including integrin activation-mediated signaling, cell adhesion and migration, immune regulation, and cancer progression [ 12 – 14 ]. It was found that FERMT3 expression was down-regulated in lung cancer, and depletion of FERMT3 enhances cell proliferation, migration, and invasion in lung cancer cells [ 13 , 15 ]. Nevertheless, the role of FERMT3 in EMT and COPD has not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…So far, studies have shown that FERMT3 plays crucial roles in important physiological and pathological processes, including integrin activation-mediated signaling, cell adhesion and migration, immune regulation, and cancer progression [ 12 – 14 ]. It was found that FERMT3 expression was down-regulated in lung cancer, and depletion of FERMT3 enhances cell proliferation, migration, and invasion in lung cancer cells [ 13 , 15 ]. Nevertheless, the role of FERMT3 in EMT and COPD has not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…However, another study substantiates the downregulation of FERMT3 in melanoma, breast cancer and kidney cancer; moreover, FERMT3 can act as a suppressor to affect cancer cell proliferation, invasion and migration 14 . Intriguingly, different from the increased expression of FERMT1 in non–small cell lung cancer tissues, FERMT3 decreases in tumour tissues and is correlated with diverse immune cell infiltration 15 . Additionally, kindlin‐3 lowers the threshold for NK cell activation, implying the potential role in tumour immune 16 .…”
Section: Introductionmentioning
confidence: 88%
“…14 Intriguingly, different from the increased expression of FERMT1 in non-small cell lung cancer tissues, FERMT3 decreases in tumour tissues and is correlated with diverse immune cell infiltration. 15 Additionally, kindlin-3 lowers the threshold for NK cell activation, implying the potential role in F I G U R E 1 FERMT3 is expressed at low levels in CRC tissues and cells. A,B, The expression levels of FERMT3 in CRC tissues were analysed using the online bioinformatics database UALCAN, A, and GEPIA, B. C,D, qRT-PCR, C, and western blotting D, were used to determine the mRNA and protein levels of FERMT3 in CRC tissues and adjacent normal tissues.…”
Section: Introductionmentioning
confidence: 99%
“…The role of YES1 in BCNHL pathogenesis also needs additional investigation. FERMT2 has previously been pinpointed as a biomarker for other cancers previously including non-small cell lung cancer and prostate cancer (65,66), but not for BCNHL. FERMT2 stabilizes CTNNB1, which is a well-documented activator of oncogene transcription, and is implicated in Wnt pathway regulation (67).…”
Section: Machine Learning Predicts Novel Biomarkers Of Bcnhlmentioning
confidence: 99%